Critical analysis of locoregional failures following intensity-modulated radiotherapy for nasopharyngeal carcinoma. (January 2013) - Orlandi, Ester; Tomatis, Stefano; Potepan, Paolo; Bossi, Paolo; Mongioj, Valeria; Carrara, Mauro; Palazzi, Mauro; Franceschini, Marzia; Bergamini, Cristiana; Locati, Laura; Iannacone, Eva; Guzzo, Marco; et al.
Aim: To analyze the patterns of locoregional failure following intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma (NPC) at our institution, as part of an internal quality assurance program. We aimed to investigate the potential existence of a correlation between any part of the IMRT process and clinical outcome.Methods & materials: A total of 106 non-metastatic NPC patients consecutively treated with IMRT (with or without chemotherapy) were analyzed. Radiotherapy was administered using a sequential or simultaneous integrated boost approach at the total prescribed dose of 66–70 Gy (2.00–2.12 Gy per fraction). MRI studies of recurrences were recorded with the planning computed tomography studies to identify volume of failure. Recurrence-related characteristics were analyzed with respect to the original treatment. Failures were classified as 'in-field', 'marginal' or 'out-field' if at least 95, 20–95 or less than 20% of the volume of failure, respectively, was within 95% of the total prescription dose.Results: With a median follow-up of 43.4 months, 5-years local control, regional control, locoregional control and overall survival rates were 87.7, 88.0, 83.5 and 81.3% respectively. A total of 21 failures were registered in 15 patients. In particular, ten failures (47.6%) were classified as 'in-field' (seven local failures and three regional failures [RFs]), nine failures (42.9%) as 'marginal' (five local failures and four RFs) and only two failures (9.5%) as 'out-field' (both RFs). The most relevant causes of failures were suboptimal target definition and target coverage as well as a longer than planned overall treatment time.Conclusion: IMRT determines excellent outcome in NPC patients. However, great attention in all IMRT steps is necessary to reduce potential causes of failure.